Cultivation of Chlorella vulgaris in Aquaculture Wastewater for Protein Production (2018)
Microalgae have emerged as environment friendly alternative source of valuable products for energy, pharmaceutical and cosmetic industries. These microorganisms have been also studied in wastewater treatments due to its ability to remove CO2, nitrogen, phosphorus, and toxic metals. In this work, cultivation of microalgae Chlorella vulgaris was carried out in aquaculture wastewater in order to reduce its contents of NO3 and PO4. In addition, different concentration of inorganic carbon sources (NaHCO3 and Na2CO3) and addition times were considered for determining suitable conditions in microalgae culture to produce proteins. It was found that highest protein content (45 % w/w) was achieved at 3.4 g/L of NaHCO3 and 19 h of addition time.